Efektivitas Model Pembelajaran STEAM (Science, Technology, Engineering, Art, and Mathematics) terhadap Hasil Belajar Matematika Sekolah Dasar - Sakinah Novia Dewi; Wulan Sutriyani (Jurnal Syntax Admiration, 2024)
One of the many abilities needed by students in the 21st century is problem-solving skills, especially in the teaching and learning process of mathematics. As for STEAM, which is an approach that connects the concepts of insight, technology, engineering, art and mathematics, so that students gain insight based on the learning process experienced, this learning process is a learning process when students experience learning directly so that they gain experience in their surroundings. The approach used in this learning is that students can show by explaining critically, techniques to math. Teaching various problems for math exercises with various methods that do not motivate students to participate in learning and still use the lecture method where only the teacher is active without involving students causing students to be passive and resulting in monotonous learning. The research was conducted at MI Hidayatul Husna Krasak. This research has the aim of making STEAM effective as a learning method that can affect student learning outcomes in mathematics lessons with space building material in elementary school. Students in this study used as many as 20 people with the sample collection technique used, namely purposive sampling.